2016
DOI: 10.1121/1.4954746
|View full text |Cite
|
Sign up to set email alerts
|

Level variations in speech: Effect on masking release in hearing-impaired listeners

Abstract: Acoustic speech is marked by time-varying changes in the amplitude envelope that may pose difficulties for hearing-impaired listeners. Removal of these variations (e.g., by the Hilbert transform) could improve speech reception for such listeners, particularly in fluctuating interference. Léger, Reed, Desloge, Swaminathan, and Braida [(2015b). J. Acoust. Soc. Am. 138, 389–403] observed that a normalized measure of masking release obtained for hearing-impaired listeners using speech processed to preserve tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Similar effects of positive MR PCT , again tempered by a corresponding decrease in continuous-noise performance compared to unprocessed speech, were observed by Reed et al (2016) for two other types of processing which effectively removed variations in amplitude of the speech signal. These methods included infinite peak clipping to achieve a reduction in amplitude variation similar to that present in TFS speech and a 40-band envelope signal that was reprocessed with Hilbert-transform-based TFS processing to remove the amplitude variations.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Similar effects of positive MR PCT , again tempered by a corresponding decrease in continuous-noise performance compared to unprocessed speech, were observed by Reed et al (2016) for two other types of processing which effectively removed variations in amplitude of the speech signal. These methods included infinite peak clipping to achieve a reduction in amplitude variation similar to that present in TFS speech and a 40-band envelope signal that was reprocessed with Hilbert-transform-based TFS processing to remove the amplitude variations.…”
Section: Introductionmentioning
confidence: 51%
“…The advantage of EEQ processing over peak-clipping is that it does not introduce major distortions due to the processing itself. Evidence of the greater distortions present in peak-clipping compared to EEQ processing is seen by its lower performance compared to UNP speech in continuous noise backgrounds at a given SNR (see Reed et al, 2016), whereas no significant differences were observed between CON scores for EEQ and UNP speech (see left panel of Fig. 3 above).…”
Section: B Comparison With Other Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies of Léger, Reed, Desloge, Swaminathan, and Braida (2015) and Reed, Desloge, Braida, Léger, and Perez (2016) suggest that MR for listeners with HI may be enhanced by processing methods which lead to a reduction of the normal level variations present in speech. In these two studies, however, the improvements in MR arose primarily from decreased performance in continuous background noise relative to that in interrupted noise, due to distortions introduced by the signal processing.…”
Section: Introductionmentioning
confidence: 99%